2011
DOI: 10.1021/am201166m
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Synthesis of PEG-Coated Magnetite (Fe3O4) Nanoparticles and Their Prevention of the Reduction of Cytochrome C

Abstract: We report here a facile and green synthetic approach to prepare magnetite (Fe(3)O(4)) nanoparticles (NPs) with magnetic core and polyethylene glycol (PEG) surface coating. The interaction of the bare and PEG-coated Fe(3)O(4) NPs with cytochrome c (cyt c, an important protein with direct role in the electron transfer chain) is also reported in this study. With ultrasonication as the only peptization method and water as the synthesis medium, this method is easy, fast, and environmentally benign. The PEG coated N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
123
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(141 citation statements)
references
References 50 publications
8
123
0
2
Order By: Relevance
“…Calculation of crystal size based on the peak is highest in reflection plane of the (311) The greater the concentration of PEG is added, the lesser of the saturation magnetization where the polymer coat the nanoparticles so that giving a protection effect from the magnetic field [24]. The saturation magnetization value is similar to the other reference [20,25]. Their study reported Fe 3 O 4 modified with sodium citrate and oleic acid with various concentrations of Fe 3 O 4 showed magnetization saturation of 50.61 -61.36 emu/g [25].…”
Section: Results and Discussion Characteristic Of Fe 3 O 4 -Peg 4000mentioning
confidence: 93%
See 1 more Smart Citation
“…Calculation of crystal size based on the peak is highest in reflection plane of the (311) The greater the concentration of PEG is added, the lesser of the saturation magnetization where the polymer coat the nanoparticles so that giving a protection effect from the magnetic field [24]. The saturation magnetization value is similar to the other reference [20,25]. Their study reported Fe 3 O 4 modified with sodium citrate and oleic acid with various concentrations of Fe 3 O 4 showed magnetization saturation of 50.61 -61.36 emu/g [25].…”
Section: Results and Discussion Characteristic Of Fe 3 O 4 -Peg 4000mentioning
confidence: 93%
“…PEG is long polymer chains with several advantages for coating Fe 3 O 4 of non-toxic in a large extent, non-immunogenic, non-antigenic, and proteinresistant polymer [16,20]. In addition, the incorporation of inorganic and organic particles has combination of the properties of inorganic particles such as thermal, mechanical, magnetic, and the properties of organic particles that is flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…The mass residues at 600 C were found to be 95.1% and 94.5% for stretching vibrations, and the peaks at 1103 cm À1 , which correspond to C-O-C stretching are the strong evidence for the presence of PEG molecules on the Fe 3 O 4 surface. 16 The X-ray diffraction patterns of PEGylated Fe 3 O 4 nanoparticles are shown in the inset of Figure 3. The reflections are indexed within the expected spinel type structure of the space group Fd3m.…”
Section: Resultsmentioning
confidence: 99%
“…Restricting the size to below that of the single domain size ensures super paramagnetic property, this coupled with chemical stability [6] make IONPs extremely promising for biomedical applications. Inorganic core of iron oxide, such as magnetite (Fe 3 O 4 ), and maghemite (γ-Fe 2 O 3 ) coated with a polymer such as chitosan [7] dextran [8], poly (ethylene glycol) (PEG) [9] and poly(ethylenimine) (PEI) [10], have been reported earlier. Another method for forming monolayers is by self-assembly ligand exchange for noble metal nanoparticles, where, the thiol groups attach strongly to the surface.…”
Section: Introductionmentioning
confidence: 90%